Study of Fishing Ground Determination Based on Chlorophyll-a Distribution in Sibolga Waters using Aqua Modis Satellite - Pasaribu, Parlin S; Mubarak, Mubarak; Galib, Musrifin (Journal of Coastal and Ocean Sciences, 2021)
This study aims to determinate the fishing ground, based on chlorophyll-a distribution in Sibolga marine waters every month throughout 2019 using Aqua Modis Satellite. The method used in was survey method and room analysis method to know directly of fishing ground determined by fisherman and to analysed satellite aqua modis imagery. The water quality measurements were carried out to describe of general conditions research area. The parmeters measured include water temperature, water transparency, salinity, ph, depth and current. Sibolga sea surface temperature ranges from 26-300C, water transparency ranges from 170-210 cm. water salinity ranges between 26-29 ppt, the degree of acidity (ph) ranges from 6,8-8. The depth ranges from 15-22 m,  and current velocity 0.21-0.40 m/s. Based on the results it is known that the chlorophyll-a concentration a ranges from 0.001 to 5,000 mg/m3. Highest chlorophyll-a concentration occurs in October with a range of 3,500 to 5,000 mg/m3, while the lowest chlorophyll-a concentration occurred in February with a range 0,001 to 0,500 mg/m3. Based on the chlorophyll-a average troughout the year the potential for fishing ground is in Sorkam and Kolang water